A highly attenuated Vesiculovax vaccine rapidly protects nonhuman primates against lethal Marburg virus challenge. - Courtney Woolsey; Robert W Cross; Krystle N Agans; Viktoriya Borisevich; Daniel J Deer; Joan B Geisbert; Cheryl Gerardi; Theresa E Latham; Karla A Fenton; Michael A Egan; John H Eldridge; Thomas W Geisbert; et al. (PLoS Neglected Tropical Diseases, 2022)
Background Marburg virus (MARV), an Ebola-like virus, remains an eminent threat to public health as demonstrated by its high associated mortality rate (23-90%) and recent emergence in West Africa for the first time. Although a recombinant vesicular stomatitis virus (rVSV)-based vaccine (Ervebo) is licensed for Ebola virus disease (EVD), no approved countermeasures exist against MARV. Results from clinical trials indicate Ervebo prevents EVD in 97.5-100% of vaccinees 10 days onwards post-immunization. Methodology/findings Given the rapid immunogenicity of the Ervebo platform against EVD, we tested whether a similar, but highly attenuated, rVSV-based Vesiculovax vector expressing the glycoprotein (GP) of MARV (rVSV-N4CT1-MARV-GP) could provide swift protection against Marburg virus disease (MVD). Here, groups of cynomolgus monkeys were vaccinated 7, 5, or 3 days before exposure to a lethal dose of MARV (Angola variant). All subjects (100%) immunized one week prior to challenge survived; 80% and 20% of subjects survived when vaccinated 5- and 3-days pre-exposure, respectively. Lethality was associated with higher viral load and sustained innate immunity transcriptional signatures, whereas survival correlated with development of MARV GP-specific antibodies and early expression of predicted NK cell-, B-cell-, and cytotoxic T-cell-type quantities. Conclusions/significance These results emphasize the utility of Vesiculovax vaccines for MVD outbreak management. The highly attenuated nature of rVSV-N4CT1 vaccines, which are clinically safe in humans, may be preferable to vaccines based on the same platform as Ervebo (rVSV "delta G" platform), which in some trial participants induced vaccine-related adverse events in association with viral replication including arthralgia/arthritis, dermatitis, and cutaneous vasculitis.